Kajian Geografi Bahasa dan Dialek di Sulawesi Tenggara: Analisis Dialektometri - Susiati Susiati; Risman Iye (Kantor Bahasa Provinsi Maluku Utara, 2018)
The language uniqueness of each region shows an identity of its region, so it is important to do a study that can clearly show its uniqueness. This study aims to describe the phenomenon of language usage in several vernaculars ​​in Southeast Sulawesi by applying a triangular dialectometry analysis. The instrument of this research uses dialectometry approach. Data collection methods uses a method of field fucking (direct field method). Data of this research is analyzed by using triangle dialectomentry method. This method uses the numbers as a basis for sorting. The results showed that the overall observation point that analyzed by using dialectometry, entered in the four formulation categories, namely the formulation below 20% (no language and dialect differences, ie between the Wakatobi language Kaledupa dialect and Tomia dialect), formulation 31-50% (the difference subdilek, that is between Pancana Language and Kioko Language), formulation 51-80% (dialect difference, ie between the Wakatobi language, Tomia dialect and Pancana language; Pancana language and Wakatobi language, Kaledupa dialect; Kioko language and Wakatobi language, Tomia dialect; Wakatobi language, Tomia dialect and Cia-Cia; Cia-Cia Language and Kioko Language; Kioko Language and Tolaki Language), and formulations 81 and above (language differences, between Tolaki and Cia-Cia languages).